2019
DOI: 10.2478/jwld-2019-0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water scarcity on households’ livelihoods in Iwoye-Ketu Area of Ogun State, Nigeria

Abstract: Water is an essential commodity which affects life and livelihoods in the universe. This study examined perceived effect of water scarcity on livelihoods in Iwoye-Ketu, Ogun State. Random sampling was used to select 80 rural households and water samples for the study. Data collected were analysed using descriptive, inferential and laboratory analyses. Findings showed that the mean age of respondents was 38 years with an average household size of four persons. The major sources of water were boreholes (97.5%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, both studies emphasize the adverse effects of water scarcity on livelihoods and household well-being. Adetayo et al (2019) found that approximately 60% of respondents perceived water scarcity to have a negative impact on their livelihoods, while the current study illustrates respondents' concerns over the impacts of water scarcity on economic stability, health satisfaction, and overall quality of life. Rhue et al (2023) explored the effects of household water insecurity on child health and well-being, extending the scope beyond microbiological pathogens to encompass various health impacts.…”
Section: Discussion Of Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, both studies emphasize the adverse effects of water scarcity on livelihoods and household well-being. Adetayo et al (2019) found that approximately 60% of respondents perceived water scarcity to have a negative impact on their livelihoods, while the current study illustrates respondents' concerns over the impacts of water scarcity on economic stability, health satisfaction, and overall quality of life. Rhue et al (2023) explored the effects of household water insecurity on child health and well-being, extending the scope beyond microbiological pathogens to encompass various health impacts.…”
Section: Discussion Of Resultsmentioning
confidence: 55%
“…The study of Adetayo et al (2019) investigated the effect of water scarcity on households' livelihoods in a rural area of Nigeria. Their findings highlighted similar concerns regarding water scarcity, including insufficient rainfall, pollution of water sources, and increased population pressure.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In addition to being a vital environmental component for all living things, water also plays a significant part in the economic and social progress of the human population [15]. Water accessibility and availability are inextricably linked to socio-economic development, which encompasses advancement in the economy, well-being of people, and quality of life [16].…”
Section: Socio Economic Effectsmentioning
confidence: 99%
“…Consequently, the surface water's ability to provide rural areas with water is reduces when rainfall decreases and, eventually, surface water levels drop. This increases water scarcity and causes water insecurity in the communities [15]. The change in climatic condition, to some extend may have a significant impact on surface water availability, the increased temperature leads to an increase of evapotranspiration [15].…”
Section: Water Resources In Ukhrul Townmentioning
confidence: 99%
“…Assuming a household requires 162 litres of water per day [18], with an average sunshine hour of 6 hours per day. The site discharge rate can be expressed as [16]:…”
Section: Selecting a Submersible Pumpmentioning
confidence: 99%